Meningkatkan Pengetahuan Seksual pada Remaja melalui Edukasi Seks di Yayasan Naungan Kasih Kemuliaan - Lukman Nul Hakim Harahap; Syafirah Azra Wiguna; Tania Octa Violla; Hairani Siregar (Yayasan Literasi Sains Indonesia, 2024)
Adolescence is a transitional period between childhood and adulthood, which begins when sexual maturity occurs.. This study aims to explore the understanding of children at Yayasan Naungan Kasih Kemuliaan regarding puberty and the importance of maintaining personal boundaries. The socialization activity conducted on September 27, 2024, involved six children aged 10-18 years, through an interactive approach that included presentations, educational videos, and discussions. Initial results showed that only five of the six participants understood the basic concepts of puberty. Participants expressed feelings of anxiety and confusion regarding the changes they experienced, as well as a lack of understanding about body boundaries. The education provided emphasized the importance of knowing oneself, the right to one's body, and the ability to say